2004
DOI: 10.1007/s00221-003-1669-0
|View full text |Cite
|
Sign up to set email alerts
|

Motor planning: effect of directional uncertainty with continuous spatial cues

Abstract: We have investigated the effect of directional uncertainty on the planning of reaching movements. For this purpose, we have used sections of annuli as spatial cues to indicate the directional range within which the target would be presented. The results showed that the reaction time of the reaching response increased with cue range and with the angle between the center of the cue and the target. In addition, the initial direction of movement was biased toward the center of the cue. These results conformed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
5
9
0
Order By: Relevance
“…In the present study, target and distractor(s) were spatially compatible, i.e., in close proximity and in the same hemifield, In Cardoso-Leite and Gorea's setup, the target was presented on the central meridian and distant from the distractors' location. The present results are thus in line with previous findings showing that the presentation of a compatible distractor just before a target reduces manual reaching RTs (Bock and Arnold 1992;Bock and Eversheim 2000;Pellizzer andHedges 2003, 2004). They are also in agreement with studies showing a RT reduction to a suprathreshold target by near threshold distractors only when consciously detected (Waszak and Gorea 2004;Waszak et al 2007).…”
supporting
confidence: 93%
“…In the present study, target and distractor(s) were spatially compatible, i.e., in close proximity and in the same hemifield, In Cardoso-Leite and Gorea's setup, the target was presented on the central meridian and distant from the distractors' location. The present results are thus in line with previous findings showing that the presentation of a compatible distractor just before a target reduces manual reaching RTs (Bock and Arnold 1992;Bock and Eversheim 2000;Pellizzer andHedges 2003, 2004). They are also in agreement with studies showing a RT reduction to a suprathreshold target by near threshold distractors only when consciously detected (Waszak and Gorea 2004;Waszak et al 2007).…”
supporting
confidence: 93%
“…Consistent with this idea, Tse, Sheinberg and Logothetis ( 2003 ) reported poorer change detection performance along the vertical than the horizontal axis, a finding they attributed to the relatively poor spatial resolution of attention along the vertical dimension (e.g., He, Cavanagh, & Intriligator, 1996 ). Furthermore, Pellizzer and Hedges ( 2003 , 2004 ) reported that reaction time of reaching responses towards visual targets increased with positional uncertainty. This finding conformed to the predictions of a capacity-sharing model, which assumes that the processing resources for motor localization are limited, and that they are distributed as a function of the spatial distribution of the possible target locations.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, there is a large fronto-parietal network that is involved in the evaluation of the probability of an upcoming motor response. We have investigated in previous studies the effect of spatial uncertainty about the location of the upcoming target by varying the number of locations (Pellizzer and Hedges, 2003;Tzagarakis et al, 2010;Tzagarakis et al, 2019), or the size of the sector of space (Pellizzer and Hedges, 2004;Tzagarakis et al, 2015) where the upcoming target could be presented. We have shown that the power of the peri-Rolandic beta-band during motor preparation decreased further, the less uncertain the location of the upcoming target was (Tzagarakis et al, 2010;Tzagarakis et al, 2015;Tzagarakis et al, 2019).…”
Section: Reliability Of Informationmentioning
confidence: 99%